Pengembangan Wisata Religi Dalam Meningkatkan Pendapatan UMKM: (Kajian di Masjid Syahrun Nur) - Hannum Harahap, Novita; Mustapa Khamal Rokan; Muhammad Lathief Ilhamy Nasution (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2024)
This research aims to find out how the development of religious tourism can increase UMKM income using SWOT analysis. The research location is the Syarun Nur Mosque and the object of this research is the development of religious tourism in increasing the income of UMKM. Based on the research results, it is known that the strategy for developing religious tourism at the Syahrun Nur Mosque in increasing UMKM income can be carried out with 4 strategies, namely providing infrastructure and arranging and repairing the facilities and infrastructure of the tourist attraction, improving services for visiting tourists, developing the business of UMKM actors around the Great Mosque. Syahrun Nur, and developing UMKM and business actors who produce and provide souvenirs and culinary specialties from the Syahrun Nur Mosque).